Influenza coverage rates in subjects with chronic heart diseases: results obtained in four consecutive immunisation seasons in the Local Health Unit of Ferrara (North Italy)" - Armando Stefanati; Silvia Lupi; Gianluca Campo; Silvia Cocchio; Patrizia Furlan; Vincenzo Baldo; Giovanni Gabutti (BMC, 2020)
Abstract Background Seasonal influenza epidemics yearly affects 5-15% of the world's population, resulting in 3-5 million serious cases and up to 650,000 deaths. According to the 2017-2019 Italian National Immunisation Plan, free immunisation is offered to the categories at increased risk of experience the complications of the infection (over 65 years old subjects, pregnant women and individuals with underlying conditions, including chronic heart diseases). Rising evidence suggests that influenza can trigger adverse cardiovascular events therefore the vaccination is recommended for secondary prevention of cardiovascular diseases. Despite this, the influenza coverage rate in subjects with chronic heart disease is underestimated. Methods The study investigated the coverage rate in four consecutive influenza seasons (from 2011/2012 to 2014/2015) in subjects that benefit from exemption from paying healthcare costs for chronic heart disease living in Local Health Unit (LHU) of Ferrara (Italy), comparing the databases of exemptions and immunisations. Results The levels of influenza vaccine uptake were unstable, reaching the 50.3% in 2011/2012 immunisation season and falling to 42.2% in the following year. Coverage rates increased with increasing age, without achieving the 75% target, neither in over 65 years old subjects. The logistic regression analysis showed that influenza coverage rates were statistically significant different (p < 0.0001, 0.003 only for category of disease in 2011/2012 immunisation season) according to age, district of residence, category of chronic heart disease and length of exemption, but not influenced by gender. Conclusions The recommendation of influenza immunisation was weakly followed in individuals with chronic heart diseases. A collaboration between cardiologists, GPs, scientific societies and patient associations could successfully support influenza vaccine uptake.